Sleep quality during pregnancy following assisted reproductive technology and natural conceiving: a prospective birth cohort study - Xie, Yidong; Peng, Ruoti; Xiao, Li; Li, Shangwei; Li, Xiaohong (Frontiers in Endocrinology, 2025)
PurposeTo investigate the association of sleep quality during pregnancy on in vitro fertilization/intra-cytoplasmic sperm injection (IVF/ICSI) and natural conceiving (NC), as well as anxiety, depression, and perceived stress.MethodsThis prospective cohort study includes 500 infertile pregnant women undergoing IVF/ICSI and 678 NC women in a Sichuan birth cohort. Data on sleep, anxiety, depression, and stress was collected in the first trimester (T1), second trimester (T2), and third trimester (T3) using integrated questionnaires. Sleep quality is quantified by the Pittsburgh Sleep Quality Index (PSQI) with a cut-point of 5 indicating poor sleep. The Self-rating Anxiety Scale (SAS), the Center for Epidemiologic Study of Depression scale (CES-D), and the Perceived Stress scale (PSS) were used for assessing anxiety, depression, and perceived stress symptoms. Additionally, the matched husbands are surveyed. Multivariable logistic regression models with adjustments for influencing factors were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the associations of sleep quality.ResultsIn the IVF/ICSI group, 61.1%, 55.5%, and 66.5% of participants in T1, T2, and T3 reported poorer sleep quality compared to the NC group, which had 43.2%, 37.4%, and 46.4% throughout the same trimesters. Additionally, the IVF/ICSI group exhibited higher levels of negative psychological factors as measured by the CES-D and PSS during T1 and T2, showing statistical significance in T1 (P = 0.008, P < 0.001) and T2 (P = 0.038, P < 0.001), except at T3 (P = 0.107, P = 0.253). In addition to psychological factors and IVF/ICSI treatment, poor sleep quality was also associated with advanced age. However, there was no significant difference in sleep quality between the husbands of the IVF/ICSI and NC groups.ConclusionThe study reveals that women receiving IVF/ICSI treatment are at a higher risk of experiencing sleep disturbances throughout their pregnancy compared with women with natural conception. While partners typically do not report major sleep problems, they do exhibit increased anxiety levels. These findings underscore the necessity for screening and addressing sleep issues in women pregnant through assisted IVF/ICSI treatment, to promote their well-being during this critical period.